2019
DOI: 10.1108/ijchm-10-2017-0661
|View full text |Cite
|
Sign up to set email alerts
|

Testing an attribute-benefit-value-intention (ABVI) model of local food consumption as perceived by foreign tourists

Abstract: Purpose This study aims to examine the attribute-benefit-value-intention (ABVI) model of local food consumption as perceived by foreign tourists. The model was designed to test the structural relationships between local food attributes, perceived benefits, consumption value and behavioral intentions. Design/methodology/approach The structural relationships of foreign tourists’ perceptions of local food consumption were conceptualized, and hypotheses were proposed. The main survey was conducted using a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 54 publications
(79 reference statements)
7
63
2
1
Order By: Relevance
“…Overseas tourists' experience of local cuisines augments new experiences of learning and adaptation beyond desires to dissipate hunger or gain nutritional value (Long, ). As a consequence, the motivation to understand the tradition of local food through consuming exotic cuisine in an overseas tourism location is consistent with providing epistemic benefits, such as satisfying knowledge about the local food culture, which heightens curiosity and novelty (Kim & Choe, ).…”
Section: Local Food Gastronomy and Its Effects On Intentions For Recomentioning
confidence: 99%
See 3 more Smart Citations
“…Overseas tourists' experience of local cuisines augments new experiences of learning and adaptation beyond desires to dissipate hunger or gain nutritional value (Long, ). As a consequence, the motivation to understand the tradition of local food through consuming exotic cuisine in an overseas tourism location is consistent with providing epistemic benefits, such as satisfying knowledge about the local food culture, which heightens curiosity and novelty (Kim & Choe, ).…”
Section: Local Food Gastronomy and Its Effects On Intentions For Recomentioning
confidence: 99%
“…A review of local food tourism literature suggests that local food attributes can be summarized as falling into the categories of food quality, tradition, uniqueness, and service quality (Chi, Chua, Othman, & Karim, ; Kim & Choe, ; Kim & Eves, ; Verbeke & Poquiviqui López, ). Previous studies have consistently shown that positive perceptions of the quality of local food positively effects future intentions (Adongo, Anuga, & Dayour, ; Chi et al, ; Horng, Liu, Chou, & Tsai, ; Jiménez‐Beltrán, López‐Guzmán, & González Santa Cruz, ; Kim, Choe, & Lee, ; Kim & Eves, ; Mynttinen, Logrén, Särkkä‐Tirkkonen, & Rautiainen, ; Stone et al, ).…”
Section: Local Food Gastronomy and Its Effects On Intentions For Recomentioning
confidence: 99%
See 2 more Smart Citations
“…This study was conducted in Bandung, Indonesia, with research variables of Brand Image, Brand Value, Loyalty, Perceived Value, Expectation, Motivation, and Behavioural Intention. Previous research has been identifying the relationship of brand equity, motivation, expectation, and behavioural intention in Taiwan (Horng, Liu, Chou, & Tsai, 2012;Jiang, Li, Liu, & Chang, 2017); Japan (Kim, 2013); and United States .…”
Section: Introductionmentioning
confidence: 99%